Linguistic reconciliation in contexts of conflict: Tamil language learning in Sri Lanka - Perera, Niru; Khodos, Iryna (Springer Nature, 2024)
This article explores how language learning is an integral component of progressing linguistic reconciliation in contexts of war and conflict. Sri Lanka is a case where ethnolinguistic division and the devaluation of Tamil as a co-official language has led to linguistic injustice for Tamil people and users of Tamil. In the post-war landscape, government commitment towards addressing this injustice, and reconciliation for that matter, has been weak. We interviewed 12 adult students and teachers in a small, non-profit, Tamil language course to understand what motivates people to learn Tamil in this context. The language course was a space where both second language and heritage language learners came together. Thematic analysis of the interview data showed that language learning motivations extended beyond the norm of the instrumental/integrative dichotomy and revealed the role of social, historical, and political factors, and a shared vision for societal multilingualism in shaping learners’ motivations. The results help to form a preliminary conceptualisation of linguistic reconciliation and to promote language learning “of the enemy” as an integral and impactful component.